Analisis Kebutuhan Air Irigasi Dengan Metode Kp-01 dan Aplikasi Corpwat 8.0 di Wilayah Indramayu Bagian Barat - Syafira Luthfi Aini; Elang Ramdhan Nur S; Ohan Farhan (Pusat Publikasi Nusantara, 2025)
This study analyzed the irrigation water needs in the western region of Indramayu, Indonesia, using the KP-01 method and the CROPWAT 8.0 application. The main focus of this study is the importance of effective water management in agriculture, especially in the midst of increasing demand and climate change. Climatological data, soil characteristics, and crop information are collected to estimate irrigation needs. The results show that CROPWAT 8.0 is superior to the KP-01 method in terms of resource use efficiency, ease of use, flexibility, and reproducibility of results. CROPWAT 8.0 recorded the highest irrigation needs in January, while the KP-01 method recorded the highest in September. Although KP-01 provides more accurate and regulatory compliant water demand figures, CROPWAT 8.0 is more efficient for large-scale data processing. Daily evapotranspiration (ETo) variations ranged from 2.6 mm/day to 4.0 mm/day, with the highest ETo occurring in December. The highest irrigation water demand was recorded in September (1,850 ltr/second/ha) and the lowest in June (0,199 ltr/second/ha). The ETo calculation using CROPWAT shows an annual average value of 4.84 mm/day, with fluctuations affected by temperature, humidity, and solar radiation. The findings aim to optimize water resource management and increase agricultural productivity in the region. The selection of the right method depends on the specific needs and applicable regulations.